Some class of real sequences having indefinite Hankel forms - Strauss, V. A.; Navarro, L. J. (Methods of Functional Analysis and Topology, 2011)
In this paper we generalize the results given in [14] about real sequences which are not necessarily positive (i.e, they are not sequences of power moments) but can be mapped, by a difference operator, into a power moment sequence. We prove by elementary methods that the integro-polynomial representation of such sequences remains after dropping the condition on its growth imposed in the mentioned article. Some additional results on the uniqueness of the representation are included.